The Influence Of Growth Opportunities, Corporate Governance, And Profitability On Company Value In Food And Beverage Companies With Capital Structure As A Moderating Variable - Ni Made Dewi Santi Yuditia; Wirawan Suhaedi (Cita Konsultindo Research Center, 2024)
This research aims to determine the influence of growth opportunities, corporate governance and profitability on company value which is moderated by capital structure. The population in this study used 84 non-cyclical consumer companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the 2020-2022 period. A sample of 27 companies used a purposive approach. Panel data regression and Moderated Regression Analysis (MRA) are used as analysis techniques. The results show that growth opportunity has a significant positive relationship to company value, corporate governance and profitability have a positive and insignificant relationship to company value. Capital structure is not significant as a moderator of the relationship between growth opportunity, corporate governance and profitability on company value.